Механика жидкости и газа: учебник - Аверин С. И. Сергей Иванович; Минаев А. Н. Анатолий Николаевич; Швыдкий В. С. Владимир Серафимович; Ярошенко Ю. Г. Юрий Гаврилович (Москва, Металлургия, 1987)
Авт. указ. на обороте тит. л.